Marketing and sales at Kublai Khan Mongolian Restaurant - Beba, Sophia M. (Iloilo City University of the Philippines Visayas, 2008)
The study on sales and marketing at Kublai Khan Mongolian restaurant was conducted to address the need to find out the marketing practices, customer behavior and sales at the restaurant. Specifically, it seeks to find out the following : what are th marketing at Kublai Khan Mongolian restaurant? ; how is customer behavior at the restaurant? ; what is the level of sales at the restaurant?. The main objective of the study is to find out the marketing practices, customer behavior and volume of sales of the restaurant. Specifically, it aims : to describe the marketing practices at Kublai Khan Mongolian Restaurant ; to describe the customer behavior at the restaurant ; to assess the volume of sales. The results of the study will help Kublai Khan management position itself in the market. Identifying its strengths and growth areas can lead to better strategies that increase customer satisfaction. The study will also help identify posible opportunities for expansion. Advertising strategies that appel most to customers can be designed to attract more clients. Most importantly. the findingd of the study can assist Kublai Khan Management boost sales anf profitability. This study, as it evaluated how Kublai Khan Restaurant attract customers and provide them satisfied services with their present marketing mix, applied an ethnographic form of research. Ethnography was employed as a technique for the study of the accomplishment of Kublai Khan Restaurant in delivering services for customer satisfaction, how it gained a niche in the fast-food chain business in Iloilo. Data was collected by each researcher through customer-observation in the store. Researchers engaged in conversation in different levels of formlity with the customers guided by the main focus of the study which was the restaurant's marketing mix. Information at the same time was solicited from the management, particularly from the store supervisor. The store supervisor was interviewed using information from customers to elicit clarification and deeper understanding for analysis of the researchers. Data gathered in the form of observational transcripts and interviews was analyzed descriptively. Output was documented in a write-up structure. Observedd situations of the everyday operations of the store, marketing mix which appealed most to customers and their satisfaction, that had established a pattern that aided the researchers in data analysis and a possible theory development of the restaurant's success would be reflected st the end of the study. Results shown that there were different reactions and impressions of the reaturant based on the type of customer and frequency of his/her visit. Thus, at the end of the study, customrs were ctaegorized as first-timers, repeat and loyal/regular customers (those who come to the restaurant almost everyday). The interviews also reealed how these customers known about Kublai Khan and who brought them their, mostly friends and families. Likewise, for each category, different part of the marketing mix lso appealed to them. Most first timers found it hard to make an order, not having in mind the idea of the menu, especially of the buffet. While repeat and loyal customers were highly satisfied of the restaurant service and its amenities and were mostly buffet lovers. The main reason why they became loyalists. Almost everybody agreed that product prices were affordable. some said the place was cozy and ambiance was good. However, many complained of the physical arrangements of table and chairs, they were put too close each other. For first timers and some repeat customers, service were okay, while loyal customers were highly satisfied. Most of them were treated personally by each staff, knowing their food and service preferences. However,promotional strategies of the restaurant was ineffective and insufficient to drive in more customers. In addition, customers provided insights and suggestions for improvement. Some said product development must be made. Kublai Khan must create a menu that will provide name recall. Assistance in making orders through describing the dishes and recommending some should be employed especially for first timers. They also suggest to arrange the place and provide spaces between tables and chairs. Service wise, faster delivery of orders will be highly appreciated.
Keywords: Kublai Khan Mongolian Restaurant